Adult Children's Migration and Well-being of Left Behind Nepalese Elderly Parents - Saruna Ghimire; Devendra Raj Singh; Dhirendra Nath; Eva M. Jeffers; Maheshor Kaphle (Springer, 2018)
The objective of this study is to assess whether adult children's migration is associated with overall well-being of left-behind elderly parents in Nepal. A cross-sectional house-to-house survey was conducted among 260 community-dwelling elderly residents of Krishnapur municipality, Nepal. Binary logistic regression was used to identify whether migration of adult children was associated with elderly parent's self-reported chronic diseases, depressive symptoms, perceived loneliness and social support. More than half of the study household (51.2%) had at least one adult migrant child. Compared to participants without a migrant child, participants with a migrant child had higher odds of self-reported chronic diseases (OR = 1.79, 95%CI: 0.91-3.54), presence of depressive symptoms (OR = 1.07, 95%CI: 0.64-1.77), and self-perceived loneliness (OR = 1.23, 95%CI: 1.06-1.42) but except for loneliness, the odds ratio for other indicators of well-being were not statistically significant. Although the literature posits an inverse relationship between adult children's migration and the overall well-being of the elderly parents, in our study, adult children's migration was not associated with inverse health outcomes among study participants. However, from a policy perspective, it should be understood that these observations may be transient since the family structure of Nepalese society is rapidly changing.